Ælfric’s De Temporibus Anni. Edited by Martin Blake - Roberts, Jane (The journal of theological studies, 2010)
Ælfric’sDe temporibus anni is a curiosity, a brief and orderly summary of essential general scientific knowledge distilled principally from Bede’s writings. As Martin Blake points out (p. 66), Ælfric does not aspire ‘to the heights of scientific learning’ seen in Bede’s De temporum ratione. Rather, the indications are of ‘an educational curriculum in England at the time which had limited ambitions in this area’. In Cambridge, University Library, Gg. 3. 28, where the De temporibus anni follows directly at the end of the second series of his Catholic Homilies, Ælfric himself tells us that his short treatise (‘lytel cwyde’) is not intended as a homily.